"Rural but not rural": gendered and classed moral identities in liminal spaces in Guangdong, China. Issue 2 (4th March 2022) - Lui, Lake; Chan, Kam Wing
ABSTRACT: China is woven into the fabric of territorial demarcation between rural and urban space, which shapes people's life chances. Grounded in the study of rural-urban and local/non-local inequalities, we explore the identity constructions of people-in-between – rural local villagers (commonly named "urban villagers") in chengzhongcun (villages-in-the-cities). Based on in-depth interviews and participant observations in Shenzhen and Guangzhou, we found stereotypes of rural local people's as ill-mannered and lazy; yet economically well-off. Women and men who considered themselves rural locals challenge the stereotype by drawing upon the gender- and class-appropriate understandings of their identities. Rural local women crafted a "model woman discourse" by emphasizing their traditional Chinese feminine traits, othering rural migrants for manipulating sex for upward mobility, and criticizing urban women for being too assertive in relation to men. Some rural local men, in contrast, created a subculture that defined their version of success; others embraced urban masculinity. In any case, the processes of identity construction often reinforce stereotypes based on rural/urban and local/non-local divide, class, and gender.